Magnetic Nanoparticles Coated with Cationic Polymer and Label-Free Peptide Aptamer for Selective Adsorption with Bisphenol A - Tummachote, Jakkrit; Rutnakornpituk, Boonjira; Rutnakornpituk, Metha (Trends in Sciences, 2023)
Magnetite nanoparticles coated with quaternized poly(diethylamino)ethyl methacrylate (PDEAEMA) (PQDEA@MNP) and functionalized with bisphenol A (BPA)-specific peptide aptamer (CKSLENSYC) were synthesized and used as nano-adsorbents for selective adsorption with BPA. The polymer coated on the particles provided their good stability and dispersibility in water, and the aptamer provided selective adsorption with BPA targets. Fourier transformed infrared spectrophotometry (FTIR), thermogravimetric analysis (TGA) and vibrating sample magnetometry (VSM) techniques confirmed the presence of the polymer on the particle surface. From transmission electron microscopy (TEM) study, the particle size was ca.6 - 10 nm in diameter with some nanoclustering (30 - 60 nm in diameter of the nanoclusters). The selective adsorption of BPA on the particles was predominant over the non-specific adsorption when performed in PBS buffer (pH 10) in the presence of NaCl and tween-20. The nano-adsorbents had a good linearity range for the detection of BPA between 0.04 and 0.20 ppm with limit of detection (LOD) of 0.0145 ppm. They retained good BPA adsorption efficiency even when other interfering molecules were present. This simple measurement with the use of these nano-adsorbents without molecular labelling might be promising solid supports for use in various applications with good tolerance towards interfering molecules. HIGHLIGHTS Magnetic nanoparticle was coated with cationic polymer and BPA-specific aptamer This label-free peptide aptamer allowed for the selective capture of BPA targets It showed high selectivity to BPA capture and good tolerance to interfering molecules GRAPHICAL ABSTRACT